A Case Study of Severe PM2.5 Event in the Gwangju Urban Area during February 2014 2014년 2월 광주 도심에서 발생한 PM2.5 고농도 사례 연구 - Yu, Geun Hye; Lee, Bok Jin; Park, Seung Shik; Jung, Sun A.; Jo, Mi Ra; Lim, Yong Jae; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2019)
Severe hazes, which are generally characterized by high concentration level of fine particulate matter (PM2.5) and visibility impairment, occurring during winter have still been a great challenge in Korea. The control strategies for air pollution in Korea were not only cutting-edge issues of PM2.5 study, but an imperative problem to be addressed to the government and the public. A severe haze event lasting approximatively 10 days occurred in February 2014 in Gwangju, Korea. Hourly measurements of PM2.5 and its chemical constituents such as organic and elemental carbon (OC and EC), ionic species, and metal species were made at the air pollution intensive monitering station in Gwangju. Over the haze event, concentrations of three secondary ionic species (=SO42-+NO3-+NH4+) and organic matter (=OC×1.6) were on average 50.3 and 18.2% of PM2.5, respectively. Hourly highest concentration among the major chemical species was SO42- with the concentration of 42.7 μg/m3 and contribution of 42.9% to the PM2.5. Organic aerosols were strongly associated with local traffic emissions, with some contribution from biomass burning activities at a rural site at northern and/or northeastern directions from the site. Another important feature found during high PM2.5 event was that SO2 and NO2 concentrations were approximately 2~4 times lower in Gwangju than those in Seoul, Daejeon, and Ulsan. However, secondary ionic species concentrations in Gwangju were significantly higher than, or similar to those in other three metropolitan areas. This could possibly be attributed to high O3 concentration (53~71 ppb) in the afternoon, enhancing the formation of SO42- and NO3- through photochemical reactions of SO2 and NO2, and finally leading to PM2.5 increase. Over the high PM2.5 event, SO42- and NO3- concentrations showed similar temporal trends, but their pollution characteristic was completely different. For example, an increasing rate in NO3- concentration was greatly influenced by both local secondary production and long-range transportation (LTP). Whereas, it was found that impact by LTP was likely an important factor to control the increase in SO42- concentration. In conclusion, it is suggested that cutting nitrogen oxides from vehicle emissions is a very important step to control winter haze event in Gwangju more effectively on local scale
Keywords: Control strategies for PM2.5; Cutting vehicle emissions; Long-range transportation; Photochemical reactions; PM2.5 event